Membrane Composition Changes and Physiological Adaptation by Streptococcus mutans Signal Recognition Particle Pathway Mutants - Hasona, Adnan (American Society for Microbiology, 2007)
Previously, we presented evidence that the oral cariogenic species Streptococcus mutans remains viable but physiologically impaired and sensitive to environmental stress when genes encoding the minimal conserved bacterial signal recognition particle (SRP) elements are inactivated. Two-dimensional gel electrophoresis of isolated membrane fractions from strain UA159 and three mutants (Δffh, ΔscRNA, and ΔftsY) grown at pH 7.0 or pH 5.0 allowed us to obtain insight into the adaptation process and the identities of potential SRP substrates. Mutant membrane preparations contained increased amounts of the chaperones DnaK and GroES and ClpP protease but decreased amounts of transcription- and translation-related proteins, the β subunit of ATPase, HPr, and several metabolic and glycolytic enzymes. Therefore, the acid sensitivity of SRP mutants might be caused in part by diminished ATPase activity, as well as the absence of an efficient mechanism for supplying ATP quickly at the site of proton elimination. Decreased amounts of LuxS were also observed in all mutant membranes. To further define physiological changes that occur upon disruption of the SRP pathway, we studied global gene expression in S. mutans UA159 (parent strain) and AH333 (Δffh mutant) using microarray analysis. Transcriptome analysis revealed up-regulation of 81 genes, including genes encoding chaperones, proteases, cell envelope biosynthetic enzymes, and DNA repair and replication enzymes, and down-regulation of 35 genes, including genes concerned with competence, ribosomal proteins, and enzymes involved in amino acid and protein biosynthesis. Quantitative real-time reverse transcription-PCR analysis of eight selected genes confirmed the microarray data. Consistent with a demonstrated defect in competence and the suggested impairment of LuxS-dependent quorum sensing, biofilm formation was significantly decreased in each SRP mutant.